Erecting “an instructive object”: The Case of the Halifax Memorial Tower - Williams, Paul (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2007)
Abstract In 1912 the Halifax Memorial Tower was unveiled to commemorate the 250th anniversary of the first “representative government” in the British Empire – in Halifax, Nova Scotia, in 1758. Unlike most monuments of its time, it did not celebrate great men, important battles, the monarchy or colonization. Instead, it was meant to mark a political moment in the nation’s past and to valorize the ongoing democratic process in the newly confederated Dominion of Canada. In this sense, it was as much a symbol of progress as it was a monument to past glories.